Learning AutoCAD : working with reference - Bryant, Shaun (InfiniteSkills, 2013)
"In this AutoCAD - Working with References training course, expert author Shaun Bryant teaches you everything you need to know about references in AutoCAD. This training course is designed for users that already have a fundamental understanding of working in AutoCAD. You will start by learning the basics of working with references, such as how to use the reference panel and reference fading. You will then learn about the reference palette, including how to attach references, refresh and reload, and work in the details panel. Shaun will teach you about various reference details, which include attachments, overlays, scale, and rotation. In this video tutorial, you will work with XREFs, and learn how to unload, detach, bind, and update an XREF. Shaun will teach you about underlays, showing you how to adjust, clip, and scale an underlay. Finally, you will learn how to plot with XREFs using layers, layer states, and layer property and group filters."--Resource description page.